Analisis SWOT Pada KSPPS BKK Bersama Kami Kasembadan Purwokerto - Fauzi, Hafiz Zaki; Aflah, Nafilah; Setyamien, Salsabila Khairunisa; Shafrani, Yoiz Shofwa (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2025)
This research was conducted with the aim of identifying the strengths, weaknesses, opportunities, and threats (SWOT) of KSPPS BKK Bersama Kami Kasembadan Purwokerto in the current era of digitalization. This research uses a qualitative method with a case study approach. Data collection was carried out directly to the Manager of KSPPS BKK Bersama Kami Kasembadan. The results of the study showed that the total score of the IFAS matrix (strengths and weaknesses) was 2.58, which means that KSPPS has quite strong internal potential, although there are still a number of weaknesses that need to be fixed to increase competitiveness. While the total score of the EFAS matrix (opportunities and threats) was 2.55, which means that KSPPS is quite capable of utilizing external opportunities and is quite effective in dealing with threats in the external environment, but there is still room for improvement. Therefore, the right SWOT strategy to apply is an aggressive or growth strategy with a Strengths and Opportunities (S-O) pattern, namely expanding the market, especially among Muslim communities who are increasingly aware of the importance of Islamic finance, establishing cooperation with Islamic schools and religious communities using a reputation for healthy and stable financial management as an attraction, as well as traditional trader markets with a personal approach based on practical and easy-to-understand product strengths.